Distribution facility : resource utilization and optimization study - Prashanth Menon. (2008)
This case study looks into the capacity and resource planning for the Distribution Centre facility at ACME Distribution Co. The aim is to examine and find out the optimal VNA (Very Narrow Aisle) machine to deploy in relation to the Distribution Centre's occupancy and activity levels and analyse the current work flow and provide recommendations for improvement. The study attempts to determine if the DC is operating at the effective capacity level relative to the design capacity levels. It also identifies the impact of an incremental increase in inventory turn on the additional working hours required to be put in by the staff at ACME Distribution Co. without increasing the current resources.